Culturally-biased voting in the Eurovision Song Contest: Do national contests differ? - Oliver Budzinski; Julia Pannicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2014)
The economic literature on the Eurovision Song Contest (ESC) establishes empirical evidence for culturally-biased voting, more precisely also biases based on geographical closeness, political relations, ethnical and linguistic affinity. The Bundesvision Song Contest (BSC), a similar contest with principally the same rules but organized on the national level in Germany, offers a unique opportunity to compare international voting bias patterns to national voting bias patterns. Thus, this paper presents an innovative analysis by comparatively analyzing the ESC's historical data from 1998 to 2013 and the BSC's data from its beginning in 2005 until 2013 with the same econometric methodology. Our results show that voting biases do not only matter in international contests but also occur in similarly-organized national contests with roughly similar magnitude and quality - despite the cultural background of participants and voters being much more homogenous.
Keywords: L82; Z10; 330; Eurovision Song Contest; Bundesvision Song Contest; culturally-biased voting; media economics; cultural economics